Casarett and Doull's toxicology the basic science of poisons - Klaassen, Curtis D. (New York McGraw-Hill Education, 2019)
The gold-standard text on the science of poisons updated to capture the latest breakthroughs and developments Casarett & Doull's Toxicology: The Basic Sciences of Poisons is the most trusted all-in-one overview of the biomedical and environmental aspects of toxicology. Presented in full color, it delivers a skill-building review of the basic components of toxicology, including general principles, modes of action, and chemical-specific toxicity. Spanning the entire field, Casarett & Doull's is considered to be the ultimate authority in toxicology. The Ninth Edition has been extensively updated by each chapter author and is enhanced by the addition of all-new chapters on timely topics such as computational toxicology and auditory toxicology. The extensive use of tables, illustrations, and other visuals make the information easy to understand and remember"--
This edition reflects the progress made in toxicology during the last few years. For example the importance of apoptosis, autophagy, cytokines, growth factors, oncogenes, cell cycling, receptors, gene regulation, protective mechanisms, repair mechanisms, transcription factors, signaling pathways, transgenic mice, knock-out mice, humanized mice, polymorphisms, microarray technology, second-generation sequencing, genomics, proteomics, epigenetics, exposome, microbiota, read across, adverse outcome pathways, high-content screening, computational toxicology, innovative test methods, organ-on-a-chip, etc. in understanding the mechanisms of toxicity and the regulation of chemicals"--
Includes bibliographical references and index.
Keywords: Toxicology; MEDICAL / Pharmacology